GAMBANG DI SUNDA - S.Sen.,M.Sn., Soleh (LP2M ISBI Bandung, 2018)
Gambang in Sunda consists of Gambang that is native to the Sunda region and originating from outside the Sunda region. The existence of the original Gambang from the Sunda region was pressured by the existence of Gambang originating from outside the Sunda region. This is due to the existence of the people who became the central.figure who encouraged the growing popularity of the xylophone from outside Sunda with the existence of the gamelan salendro.